Comparison of international wind codes for across wind response of concrete chimneys. Issue 207 (December 2020) - Rahman, Saba; Jain, Arvind K.; Bharti, S.D.; Datta, T.K.
Abstract: Lift force arises due to the shedding of vortices in the wake of structures. Flexible structures such as the chimney tend to experience aero-elastic phenomenon during the vortex-induced across wind vibration caused due to vortex induced lift forces. While rigorous theoretical analysis including the aero-elastic effect is desired for the validation of the design of the chimney and for performing the reliability analysis, the initial design of the chimney for wind induced forces is routinely performed using code provisions. Almost all the countries have their codes for considering the wind loads on chimneys. For the design of tall chimneys for across wind forces, different codes differ in their approaches and provide different code provisions. The objective of the present paper is to compare seven major international code methods for the design of reinforced concrete chimneys for across wind forces and to present the basis of the formulations of their code provisions. They include the CICIND-2011, ACI 307-08, NBCC, IS 4998:2015, AS/NZ 1170.2:2011, Euro code method-I (EN 1991-1-4) and Euro code method-II (EN 1991-1-4). It is shown that the equivalent static formulas provided by different codes follow either Vickery and Basu method or Ruscheweyh's method. Further, how different code formulae are derived from these two formulations is shown while comparing different codes. The comparison of different important code provisions is illustrated and evaluated with the help of three numerical example problems. Highlights: A comparative study of major international wind codes for the analysis of reinforced concrete chimney for across wind forces. Explanation of the basis of the code provisions which follow the Vickery and Basu model, and Ruscheweyh's model. Underline ​​differences among various parameters adopted by different codes leading to the differences in responses.